The Preliminary Research of Development of Mathematics Learning Model Based Realistic Mathematical Education and Literacy in Junior High School - Rusdi; I Made Arnawa; Ahmad Fauzan; Lufri (Fakultas Ilmu Pendidikan UNP)
The research was due to Indonesian students’ literacy in mathematics was unsatisfying according to Programme for International Student Assessment. The aim of this research was to gain needs and context analysis, and literature review which based on the prominence to develop a learning model. This research belonged to descriptive study. Based on data analyzed, the findings revealed that 1.The average value of students' mathematical literacy was 31.87 be classified into low category; 2.The assessment instruments was far from the mathematical literacy; 3.The realistic mathematics education approach ever developed by the researcher in learning mathematics had not been combined with the concept of literacy; 4.The teachers needed the learning models that could improve students' mathematical literacy; 5.The students wanted contextual learning, 6) most students liked reading with audio learning styles; 7.The curriculum content which had to appropriate with the development of this model was the Linear Equation System of Two Variable; 8.The main concept was the general form of Linear Equation System of Two Variables, solution with graph, substitution and elimination. Based on these findings, the researcher needed to develop mathematics learning model based on realistic mathematical education and literacy in junior high school.